The optimum number of repetitions to be used with isokinetic training programs - Bendle, Stephen Rodney (My University, 1985)
The purpose of this study was to determine the optimal number of repetitions necessary to obtain maximal effectiveness for isokinetic training. 16 males & 23 females from the University of Wisconsin - La Crosse & the Cybex Center in La Crosse were randomly assigned to training groups of varying reps in an attempt to investigate this problem.